Mainstream (Interchange Series) Vs. Non-Mainstream (Alternative View Series) English Textbooks: Students’ Perception - Mohamed, Anes; Mohammadi, Mahtab (ELT Worldwide: Journal of English Language Teaching, 2024)
This study looked into the ways in which English as a foreign language (EFL) learners view a mainstream textbook (New Interchange Series) versus a non-mainstream (Alternative View Series). Of special focus was the students’ perception of the content of the textbooks used in the class, class activities, linguistic improvement, and overall satisfaction with the two textbooks. The participants of the study comprised 100 students who were divided into two equal groups: 50 students in the mainstream cohort and 50 in the non-mainstream cohort. The data was collected using an 11-item questionnaire designed to measure the main constructs of the study. This questionnaire was administered at the end of the course. Data analysis was done through the use of SPSS. The main findings indicate that students were more satisfied with the non-mainstream textbook (Alternative View) than the mainstream textbook (Interchange).